Factors Influencing the Secondary School Students’ Attitudes to Chemistry - Švandová, Kateřina; Kubiatko, Milan (Scientia in educatione, 2020)
The study is focused on the investigation of students’ attitudes to the subject of Chemistry on Czech secondary grammar schools. The partial aims are to find out differences between results with respect to gender, year of study and favourite subject. A questionnaire with 5-point Likert type items was used as a research tool. The sample size contained 552 Czech secondary grammar school students. By factor analysis the items were distributed into four categories: 1. The relevance of chemistry, 2. Popularity and difficulty of chemistry, 3. Chemical aids and laboratory experiments, 4. Interest in chemistry. The overall score indicated neutral students’ attitudes toward chemistry. There was a statistically significant difference between boys and girls. Boys achieved higher score in comparison with girls. Boys perceived chemistry positively and girls neutrally. The youngest students perceived chemistry positively, others had neutral attitude toward chemistry. The conclusion includes further possibilities of research in this area.